Party constitutions and political challenges in a democracy : Nigeria in the forth republic, 1999-2011 - Katsina, Aliyu Mukhtar (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
This study investigates the constitutions of the six major political parties in the Nigeria's Fourth Republic. These are the Action Congress of Nigeria, All Nigeria Peoples Party, All Progressives Grand Alliance, Congress for Progressive Change, Labour Party, and Peoples Democratic Party. It focuses on explaining the political challenges which these parties faced; how they used their constitutions in responding to these challenges; and the causes for variations in their responses. This approach, the thesis shows, is necessary for understanding the party system in Nigeria as well as the nature of its politics and democracy. Using data from party constitutions, party laws, interviews and statements of party leaders, and relevant texts and archival materials, investigation reveals that parties adopt constitutions because of the need to advertise their ideologies, legitimate their decisions, and manage internal conflicts among their members. They also adopt constitutions because of party laws, and the dictates of inter-party competition. Variations among party constitutions result from differences in their electoral success, respective age, historical experience, interests of their founders, and party laws that conditioned the perception of their environment and the challenges inherent in that environment. The study shows that differences among these parties in terms of their character and outlook, ideology and disposition, organization and governing structure, and the challenges they faced and their responses to those challenges in the Fourth Republic were insignificant. The parties were catch-all in character that relied mostly on sectional bases for their support in a volatile party system characterized by higher polarization and lower fragmentation. One disturbing trait of these parties was their propensity to violate principles of internal democracy in managing their affairs, especially in the processes of candidates' nominations, which constituted a major threat to consolidation. The Independent National Electoral Commission and other regulatory agencies need to institute measures to ensure that parties adhere to the principles of rule of law and internal democracy in all their activities. Future studies would find the framework developed by this research useful in investigating different political systems, including those with more institutionalized and competitive party systems. Comparison could be made regarding how experience of parties under different environments, party systems, and party laws produce specific responses in their constitutions.